Occupational performance coaching : a manual for practitioners and researchers - Graham, Fiona, ....-; Kennedy-Behr, Ann, 1971-; Ziviani, Jenny, ....- (Abingdon, Oxon ; : Routledge, 2021)
"This book presents a definitive guide to understanding, applying and teaching Occupational Performance Coaching (OPC). Grounded in principles of occupational therapy, person-centredness and interprofessional frameworks of health and disability, this book will be of interest across health and rehabilitation professions"--
Includes bibliographical references and index.
Keywords: Occupational therapy -- Handbooks, manuals, etc